The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/j.1681-4835.2014.tb00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Failure of an E‐Marketplace Pioneer in a Developing Country

Abstract: The purpose of this study is to understand the formation and failure of an e-marketplace pioneer in a developing country. Much of the research on e-marketplaces focuses on the developed world. Within the limited literature on the developing world, the dominant focus has been on user adoption and related constraints. Little research thus exists on how emarketplaces are formed and whether they succeed or fail. This study therefore follows qualitative interpretive case study methodology to investigate the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Armstrong Soule and Hanson (2018: 263), for example, note that marketplaces such as Facebook Marketplace , Craiglist and Buy/Sell/Trade groups are ‘geographically bound’ in terms of the communities they attract; Saarijärvi et al’s (2018) research stresses Facebook groups’ local orientation; while Podkalicka (2022) describes local, purposefully promoted, characteristics of Gumtree (Australia). Consumer studies have further considered geography in relation to the uptake of online shopping and digital marketplaces across various locations, based on context-specific socio-economic variables (Beckers et al, 2018 in Belgium; or Effah, 2014 in Ghana; Yang and Wang, 2013 in China). Many studies have confirmed the so-called ‘home bias’ – that online shoppers still have a preference for buying things closer to home – as well as the important role that language and cultural traditions play in online consumer practices (Cowgill et al, 2013; Gomez-Herrera et al 2014; Yang and Wang, 2013; Zhao et al, 2019).…”
Section: Digital Marketplaces and Geographymentioning
confidence: 99%
“…Armstrong Soule and Hanson (2018: 263), for example, note that marketplaces such as Facebook Marketplace , Craiglist and Buy/Sell/Trade groups are ‘geographically bound’ in terms of the communities they attract; Saarijärvi et al’s (2018) research stresses Facebook groups’ local orientation; while Podkalicka (2022) describes local, purposefully promoted, characteristics of Gumtree (Australia). Consumer studies have further considered geography in relation to the uptake of online shopping and digital marketplaces across various locations, based on context-specific socio-economic variables (Beckers et al, 2018 in Belgium; or Effah, 2014 in Ghana; Yang and Wang, 2013 in China). Many studies have confirmed the so-called ‘home bias’ – that online shoppers still have a preference for buying things closer to home – as well as the important role that language and cultural traditions play in online consumer practices (Cowgill et al, 2013; Gomez-Herrera et al 2014; Yang and Wang, 2013; Zhao et al, 2019).…”
Section: Digital Marketplaces and Geographymentioning
confidence: 99%
“…Effah brings into light the issue associated with research in the area of e-marketplace and argues that most of the research work in this area is with regards to developed world [29]. Only a limited research is done with respect to developing countries which is mainly focused on user adoption and the associated challenges.…”
Section: E-marketplace Adoption and Usagementioning
confidence: 99%
“…Therefore, digital and mobile technologies diminish the distance between commodity producers and consumers to connect demand and supply. The borderless and virtual business platforms allow freely interacting suppliers, customers, and competitors to reduce transition costs, inventory, and marketing costs while improving customer service and sales opportunities [11]- [13].…”
mentioning
confidence: 99%
“…Artificial intelligence systems allow for a finer discrimination between different customer groups to predict behaviour, price sensitivity, and search patterns [6], [10]. Therefore, firms in the digital economy also need to revisit their business models [1], [13], [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation